Genre and Translation Style in Chinese Translation of Hollywood Blockbuster Movie Titles in Mainland China and Hong Kong - Wong, Xin Yi; Amini, Mansour; Alipour, Maryam (Journal of Modern Languages, 2023)
The title of a movie is the first to attract the audience's attention. Poorly translated movie titles may result in a “low box office”, as translators in different countries have their styles and preferences in translating film titles, which might eventually result in different translations of the same movie title and cause confusion to the audience. This qualitative research used exploratory induction to investigate the influence of genre and translation style on the Chinese translation of Hollywood blockbuster movie titles in Mainland China and Hong Kong. Titles of 300 Chinese movies produced between 2001 and 2020 were purposefully selected from the top 50 Hollywood movies in the adventure, horror, and action genres. Genre was found to be slightly effective in the choice of translation style and strategies. Among the three genres, horror was found to have the greatest influence on the choice of translation strategy. It was concluded that translators from Mainland China were more conservative in title translation compared to translators from Hong Kong, whose attempt was to create innovative translations. The findings may have some theoretical and practical implications for film translators, book translators, advertising translators, translation trainers, and trainees.